1994
DOI: 10.1084/jem.180.6.2353
|View full text |Cite
|
Sign up to set email alerts
|

Precise prediction of major histocompatibility complex class II-peptide interaction based on peptide side chain scanning.

Abstract: SummaryWe describe here a new method for predicting class II major histocompatibility complex-binding peptides, based on the preferences observed in a systematic series of peptide binding experiments where each position in a "minimal" peptide was replaced individually by every amino acid. The DRBI*0401 peptide binding preferences were determined and incorporated into a computer program that looks through sequences for potential epitopes and assigns each a score. These scores correlate well with previously dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
197
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(204 citation statements)
references
References 21 publications
6
197
1
Order By: Relevance
“…As shown in Tables 2 and 3, when these algorithms were tested against several panels of peptides, it was found that they were in most cases able to predict binding of peptides to HLA-DR molecules with similar or higher sensitivity and specificity than other reported algorithms [32,40,42]. This was found, not only when the comparison was made against panels of peptides used to develop our algorithms, but most important, when independent panels of peptides were used.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…As shown in Tables 2 and 3, when these algorithms were tested against several panels of peptides, it was found that they were in most cases able to predict binding of peptides to HLA-DR molecules with similar or higher sensitivity and specificity than other reported algorithms [32,40,42]. This was found, not only when the comparison was made against panels of peptides used to develop our algorithms, but most important, when independent panels of peptides were used.…”
Section: Discussionmentioning
confidence: 62%
“…We believe that a key step in the deduction of our algorithms is the use of binder and non-binder peptides as well as correcting for the relative abundance of amino acids in proteins. Since our algorithms are based on blocks of 8 amino acids, but the algorithm of Southwood et al [42], of Hammer et al [40], and of Marshall et al [32] use 9, 9, and 11 amino acid blocks, respectively, we adapted their algorithms to the prediction using 8 amino acid blocks. This was done because when their algorithms were tested using blocks of 9 or 11 amino acids like in their original algorithm, the sensitivity of the predictions against the 9-mer peptides eluted from DR1 [29], DRB1*1101, and DRB1*0401 [30], was lower than the one attained using blocks of 8 amino acids (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…peptides were eluted with 0.1% trifluoroacetic acid according to standard procedures (27). Pellets processed contained 1.5 ϫ 10 9 cells from DR4 and DR4Ii transfectants and 3 ϫ 10 9 cells from DR4DM and DR4IiDM transfectants.…”
Section: Purification Of Hla-dr4 Molecules From Cultured Cellsmentioning
confidence: 99%
“…For example, the algorithm TEPITOPE, which is based on in vitro MHC/ peptide binding of designer peptides, can predict the binding potential of T cell epitopes to 25 different DRB molecules. (Hammer et al, 1994;Hammer et al, 1997;Sturniolo et al, 1999) However, the ability of this program to identify potential disease-associated epitopes with a specific MHC binding profile has not yet been tested.…”
Section: Introductionmentioning
confidence: 99%